International examples of primary care covid-19 preparedness and response: a comparison of four countries - AKMAN, MEHMET (My University, 2022)
We report the learnings gleaned from a four-country panel (Australia, South Africa, Egypt and Nigeria) sharing their countries\" COVID-19 primary healthcare approaches and implementation of policy at the World Organization of Family Doctor\"s World virtual conference in November. The countries differ considerably with respect to size, national economies, average age, unemployment rates and proportion of people living rurally. South Africa has fared the worst with respect to waves of COVID-19 cases and deaths. All countries introduced strategies such as border closure, COVID-19 testing, physical distancing and face masks. Australia and Nigeria mobilised primary care, but the response was mostly public health and hospital-based in South Africa and Egypt. All countries rapidly adopted telehealth. All countries emphasised the critical importance of an integrated response between primary care and public health to conduct surveillance, diagnose cases through testing, provide community-based care unless hospitalisation is required and vaccinate the population to reduce infection spread.